External Liberalization, Economic Performance and Social Policy. - Taylor, Lance (Oxford University Press, USA, 2001)
This text reports on a policy shift in transition and developing countries after the mid-1980s. Looking at the experiences of nine countries and the negative effects that liberalization has had on them, the book includes policy recommendations for problems and challenges posed by globalization.